Transfer pricing practices: empirical evidence from manufacturing companies in Indonesia / Batsyeba Sundari and Yugi Susanti. - Sundari, Batsyeba; Susanti, Yugi (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2016)
This study aims to analyze the whether tax, foreign ownership, bonus plans and debt covenants effects to transfer pricing in the multinational manufacturing companies in Indonesia. This study uses audited financial statement of the manufacturing companies’. The research sample used in this study is the multinational manufacturing company listed on the Indonesia Stock Exchange in the 2012-2014 periods, amounting to 111. The analysis technique used in this research is a logistic regression. The results of this study showed that the taxes and foreign ownership have a significant positive effect on the company's decision to transfer pricing while the bonus plan and debt covenant do not significantly influence the company's decision to transfer pricing.